KARAKTERISASI SENYAWA BIOAKTIF EKSTRAK DAUN SEMBUNG(Blumea balsamifera (L)DC) DARI BEBERAPA JENIS PELARUT - Ida Bagus Ketut Mantra; I Nengah Kencana Putra; Luh Putu Wrasiati (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2019)
Sembung (Blumea balsamifera (L) DC) is a species plant on Blumea genus, andAstereceae (compositae)family. The leaf of Sembung is used by human as empiric treatment with extraction or infuse techniqueto become “jamu” , its has function as functional drink, because its consist of flavonoid and alkaloidcompound, that has an antioxidant potency. The purpose of this research are to study of effect growthleaf level and some of organic solvent to characterizetion simplisia powder extract Sembung leaf. Themethode of extraction by maseration, then analyze is done such as flavonoid, phenolic total, antioxidantcapacity, vitamin C, IC50, and determine volatil compound on the best treatment by GC-MS. The resultshowed that very singnificant effect to all parameters analysis, and ethyl acetate extract on the tip ofSembung leaf is the best treatment, that consist of flavonoid (204,58 mg QE/g db), phenolic total (225,33mg GAE/ g db), vitamin C (451,92 mg/g db), antioxidant capacity (501,97 mg GAEAC/g db), and IC50%(37,09 ppm). The GC-MS analysis showed there are benzena compound, monoterpene (camphor,L-berneol), sesquiterpene (?-guaiene, caryophyllene, humulene) and diterpene (neophytadiene) on thebest treatment.